ANALYSIS OF CYBER THREAT AWARENESS LEVELS, PROTECTIVE BEHAVIOR, AND COMMUNICATION PREFERENCES AMONG THE DIGITAL SOCIETY IN SEMARANG CITY - Tika; Rizky Prawita Utami; Adi Marsoni; Anesthesia Aryan Putri; Rakesh Sitepu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Digital transformation in Indonesia has increased access to technology while also expanding the risk of cyber threats. This study aims to analyze the relationship between cyber threat awareness, protective behavior, and digital security communication preferences among the digital society in Semarang City. The research method used an explanatory quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS) through SmartPLS 4.0, involving 100 active internet users as respondents. The results show that cyber threat awareness has a positive and significant effect on protective behavior (β = 0.847; p < 0.001) and digital security communication preferences (β = 0.822; p < 0.001). However, protective behavior did not significantly affect communication preferences (β = 0.159; p = 0.234) and did not mediate the relationship between awareness and communication preferences (β = 0.135; p = 0.294). These findings indicate an intention-behavior gap where awareness has not been fully applied in safe communication behavior. Theoretically, the results of this study reinforce the Protection Motivation Theory (PMT) and Technology Threat Avoidance Theory (TTAT), while practically emphasizing the importance of improving communication-based cyber literacy and awareness to build a resilient digital society.